Brazilian Consumer Perceptions of Electric Vehicles Using LLMs on Online Comments - Oliveira, Kalidsa B. de; Lunardi, Gabriel M.; Silveira, Thiago L. T. da; Oliveira, Adriano Q.; Emmendorfer, Leonardo Ramos (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
The transition from gasoline-powered vehicles to electric vehicles (EVs) is a major step forward, driven by both technological innovations and environmental concerns. This study analyzes the perceptions of Brazilian consumers toward EVs, using a novel dataset of YouTube and Reddit comments collected between 2015 and 2025. To handle the large volume of text, we used the LLaMA 3.2 language model with custom prompts to identify and analyze specific technical aspects of EVs. Our results show that consumers’ main concerns are limited range and high cost, while the most valued aspects are energy efficiency and the technology itself.